The Effect Of Entrepreneurship Education And The Family Environment On Entrepreneurial Interest With Self-Efficacy As Moderating Variable - Sandi Cua; Yossinomita Yossinomita; Roby Setiawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research seeks to provide insight into the influence of entrepreneurship education and the family environment on entrepreneurial interest, with self-efficacy as an intermediate variable in students of Universitas Dinamika Bangsa (UNAMA). The research approach used a quantitative method, with data obtained through the distribution of questionnaires to 362 respondents. Data analysis was carried out using SEM techniques with the help of AMOS software to assess the direct and indirect relationships between variables. The results of the study show that entrepreneurship education and the family environment have a positive and significant influence on self-efficacy and entrepreneurial interest. In addition, self-efficacy acts as a mediator that strengthens the influence of these two variables on entrepreneurial interest. These findings confirm that a relevant entrepreneurial learning process and positive family support can foster students' self-confidence, which in turn encourages an increase in interest in entrepreneurship.